Electromechanical response of thin shell laminated with flexoelectric composite layer. (December 2020) - Kundalwal, S.I.; Shingare, K.B.
Abstract: Flexoelectricity is a size-dependent phenomenon which gives an electric response to the inhomogeneous strain in centrosymmetric as well as non-centrosymmetric crystalline materials. In this novel work, an analytical model was developed for the elastic shell laminated with flexoelectric graphene-based composite layer based on Kirchhoff–Love theory considering both piezoelectric and flexoelectric effects to investigate the electric potential distributions in it. Moreover, finite element (FE) models were developed to validate the analytical results. Developed models envisage the results for the distribution of electric potentials in graphene-based composite shell and results predicted by both analytical and FE models are found to be in better agreement. Our results reveal that the electromechanical behavior of laminated shell is significantly improved due to the incorporation of flexoelectric effect. The consideration of flexoelectric effect results in the increase in the values of total electric potential of laminated shell by (i) 340% for mode (1, 1), (ii) 300% when the thickness of composite layer is 15 nm, (iii) 315% when the radius of base shell is 50 nm and (iv) 244% when the shell thickness is 40 nm compared to that of conventional case (i.e., shell laminated with piezoelectric layer). The major advantage of flexoelectric layer over that of piezoelectric layer is that the former is not influenced by the in-plane strains of base shell. Highlights: The electromechanical response of thin elastic shell laminated with graphene-based composite layer/patches was studied. An analytical model was developed for the laminated shell based on Kirchhoff–Love theory to investigate response of shell. The parametric study carried out to study the effect of variation of mode numbers, patch thickness and shell radius. Results reveal that electromechanical behavior of shell is improved due to the incorporation of flexoelectric effect.